2015
DOI: 10.1090/tran/6341
|View full text |Cite
|
Sign up to set email alerts
|

Bigraphical arrangements

Abstract: We define the bigraphical arrangement of a graph and show that the Pak-Stanley labels of its regions are the parking functions of a closely related graph, thus proving conjectures of Duval, Klivans, and Martin [4] and of Hopkins and Perkinson [5]. A consequence is a new proof of a bijection between labeled graphs and regions of the Shi arrangement first given by Stanley in [8]. We also give bounds on the number of regions of a bigraphical arrangement.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Remark 5.1.3. The realizable part of the Bohne-Dress theorem states that the regular tilings of Z A by paralleletopes are dual to the generic perturbations of the central hyperplane arrangement defined by A. Hopkins and Perkinson [25] investigated generic bigraphical arrangements, i.e. generic perturbations of twice the graphical arrangement, and associated certain partial orientations, which they called admissible, to the regions in the complement of such an arrangement.…”
Section: Dilations the Ehrhart Polynomial And The Tutte Polynomialmentioning
confidence: 99%
“…Remark 5.1.3. The realizable part of the Bohne-Dress theorem states that the regular tilings of Z A by paralleletopes are dual to the generic perturbations of the central hyperplane arrangement defined by A. Hopkins and Perkinson [25] investigated generic bigraphical arrangements, i.e. generic perturbations of twice the graphical arrangement, and associated certain partial orientations, which they called admissible, to the regions in the complement of such an arrangement.…”
Section: Dilations the Ehrhart Polynomial And The Tutte Polynomialmentioning
confidence: 99%
“…(1) It is natural to ask if we can extend our results to the entire class of truncated affine arrangements; or even to subarrangements thereof. The Shi(G) arrangements [3,7] and the G-Shi arrangements [20] have garnered plenty of attention in the recent past, and remain an active area of research. A rook-theoretic perspective on them might be of interest and lend new insight.…”
Section: Final Remarksmentioning
confidence: 99%
“…The valid pair associated with R is (w, I) where w = 5 2 1 7 6 9 3 4 8 ∈ S 9 and I = [1,4], [2,7], [4,9] , and we may represent it simply by 3 : 5 2 1 7 6 9 3 4 8 .…”
Section: The Number Of Ish-parking Functions With Reverse Center Of Amentioning
confidence: 99%
“…The notion of G-parking function was introduced by Postnikov and Shapiro in the construction of two algebras related to a general undirected graph G [11]. Later, Hopkins and Perkinson [7] showed that the labels of the Pak-Stanley labeling of the regions of a given hyperplane arrangement defined by G are exactly the G-parking functions, a fact that had been conjectured by Duval, Klivans and Martin [6]. Recently, Mazin [9] generalized this result to a very general class of hyperplane arrangements, with a similar concept based on a general directed multi -graph G. Whereas Hopkins and Perkinson's hyperplane arrangements include for example the (original) multidimensional Shi arrangement, Mazin's hyperplane arrangements include the multidimensional k-Shi arrangement, the multidimensional Ish arrangement and in fact all the arrangements we consider here.…”
Section: Introductionmentioning
confidence: 99%